STRATEGI PENINGKATAN AKSES NELAYAN TRADISIONAL TERHADAP SUMBERDAYA PRODUKTIF DI DESA ROMBEN GUNA KECAMATAN DUNGKEK KABUPATEN SUMENEP - Trisna Hariyanti; Luh Putu Suciati; Anik Suwandari (UPT Penerbitan Universitas Jember, 2018)
This research aimed to Knowing the priority strategies for empowering traditional fishermen to overcome in Romben Guna, Dungkek of Sumenep. The research was conducted in Romben Guna Village, Dungkek Subdistrict with the consideration that (1) Dungkek is the district with the highest number of fishermen in Sumenep Regency, which is 4,662 people; (2) Dungkek is the second sub-district after Sapeken sub-district with the highest production of marine fish, which is 4,187.30 tons; (3) Dungkek is also the second sub-district with 11 fisheries villages after Arjasa District and (4) Romben Guna Village has high productive resource potential, in the form of siwalan trees and coconut trees. The research method used is descriptive and analytical methods. The method of data collection is done by interview using questionnaires and document study methods. Respondents were 23 people, namely 20 labor fishermen with payang fishing gear and nets and had received assistance from nets and machines from the Department of Fisheries and Maritime Affairs of Sumenep Regency, but were resold to fishermen owners and 3 expert respondents (people or parties considered to be experts in their fields ), namely 1 person from the Department of Fisheries and Maritime Affairs, Sumenep Regency, part of empowering small fishermen, 1 traditional fisherman supervisor from the supervisory community group and 1 chairman of the traditional fishing group Romben Guna Village. Data analysis using AHP (Process Hierarchy Analysis). The results showed that the priority strategy of increasing traditional fishermen's access to productive resources in the village of Romben Guna was on the dimensions of the economic aspect through equitable and sustainable credit and capital assistance through the active role of the Fisheries and Marine Agency of Sumenep Regency.